VD_FINDINFO HC / 2014 / 792 vom 13. Oktober 2014 - VD Tribunal cantonal (2014)
TRANSACTION EXTRAJUDICIAIRE, RADIATION DU RÔLE, OBLIGATION D'ENTRETIEN | 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)